Boundary Spanning Roles and Power in Educational Partnerships - Christopher M. Wegemer; Jennifer Renick (SAGE Publishing, 2021)
Research-practice partnerships (RPPs) offer promising approaches to improve educational outcomes. Navigating boundaries between contexts is essential for RPP effectiveness, yet much work remains to establish a conceptual framework of boundary spanning in partnerships. Our longitudinal comparative case study draws from our experiences as graduate student boundary spanners in three long-term partnerships to examine boundary spanning roles in RPPs, with particular attention to the ways in which power permeates partnership work. Using qualitative, critically reflexive analysis of meeting artifacts and field notes, we found that our boundary spanning roles varied along five spectrums: institutional focus, task orientation, expertise, partnership disposition, and agency. Our roles were shaped by the organizational, cultural, relational, and historical features of the partnerships and contexts of interaction. We aim to promote the development of effective RPP strategies by leveraging the perspectives and positionality of graduate students in order to advance understanding of boundary spanning roles.